Assessment of Various Mandibular Divergence Pattern or Vertical Cephalometric Pattern in Bangladeshi Adult Patients (Update Dental College Journal, 2023)
Introduction : Orthodontic diagnosis as well as the treatment planning of the patients are affected by vertical dimention of face. Lateral cephalometric radiographs are used by orthodontists to find out the norms of different skeletal, dental and soft tissue variables. Present study was undertaken with the aim to assess the various mandibular divergence pattern or vertical cephalometric pattern in Bangladeshi adult orthodontic patients.Materials and methods : This cross sectional study was conducted with 120 pretreatment lateral cephalograms of Bangladeshi adult orthodontic patients who visited Dhaka Dental College Hospital (DDCH) for orthodontic treatment for the duration of six months. The angular measurement used in this study to assess the vertical divergence pattern or vertical cephalometric pattern was mandibular plane to anterior cranial base (MP-SN). Collected data were analyzed by SPSS software version 26 and statistical significance was set as p=0.05.  Results : The study result showed that out of 120 orthodontic patients hypodivergent vertical cephalometric pattern found in 26.6% patients having ˂270 MP-SN angle and normodivergent, hyperdivergent pattern found in (45.8%), (27.5%) patients having 270 to ˂ 370 MP-SN angle and > 370 MP-SN angle respectively. Sex of the patient was not significantly associated with the vertical cephalometric pattern (as p >0.05). It was also observed that age was not statistically significantly different between male and female patients within each mandibular divergence pattern and across the three mandibular divergence patterns.Conclusion : Present study concluded that age and sex of Bangladeshi adult orthodontic patients were not significantly associated with different mandibular divergence pattern or vertical cephalometric pattern. In all the three vertical cephalometric pattern the MP-SN angle were greater in Bangladeshi female than Bangladeshi male patients.Update Dent. Coll. j: 2023; 13(2): 15-18